CultivatorFertilizer Field Tests Using a Differential Fertilization System - A. I. Derepaskin; A. N. Kuvaev; I. V. Tokarev (Сельскохозяйственные машины и технологии, 2021)
The authors carried out field tests of differentiated fertilization system "Agronavigator-Dozator" installed on a cultivator-fertilizer for intra-soil application of granular mineral fertilizers in the conditions of Northern Kazakhstan. (Research purpose) To determine the effect of differentiated fertilization system on agrotechnical, energy, operational and technological and economic indexes of the cultivator-fertilizer in field conditions. (Materials and methods) The authors carried out agrochemical soil survey according to the officially approved method. They made an electronic task map. They used the methodology for determining the conditions of field tests, agrotechnical, energy, operational and technological and energy assessments that met the current regulatory documentation requirements. Field tests of differentiated fertilization system were carried out during the second flat-cut processing of the steam field with simultaneous intra-soil granular mineral fertilizers application. (Results and discussion) The authors found out that the use of differentiated fertilization system "Agronavigator-Dozator" reduced the actual dose of application from 95 to 40 kilograms per hectare. It was determined that the presence of a parallel driving mode in the system under study reduced the amount of overlap of adjacent aisles, thereby increasing shift productivity - from 4.25 to 4.32 hectares per hour, unit energy consumption decreased from 88.1 to 86.6 megajoules per hectare, and the specific fuel consumption decreased from 14.41 to 14.16 kilograms per hectare. The economic effect of the use of differentiated fertilization system "Agronavigator- Dozator " amounted to 630.6 thousand rubles per year. (Conclusions) The authors proved that differential fertilization system "Agronavigator-Dozator" effect the actual dose of fertilization, which decreased by 57.6 percent. It was found that a decrease in the overlap of adjacent aisles increased shift productivity, reduced specific fuel consumption and specific energy consumption by 1.7 percent. It was calculated that the total sum of money was reduced by 36 percent due to the use of differentiated fertilization system "Agronavigator- Dozator".